PHENOMENOLOGY STUDY OF CORPORATE ENVIRONMENTAL RESPONSIBILITY: A FORM OF CORPORATE SOCIAL RESPONSIBILITY BY PT AMERTA INDAH OTSUKA KEJAYAN - Budianto, Risky; Triyuwono, Iwan; Mulawarman, Aji Dedi (Universitas Brawijaya, Indonesia, 2021)
This research is conducted to find deeper meaning regarding the implementation of CSR for the environment carried out by PT Amerta Indah Otsuka (Pocari Sweat) Kejayan. This research is non-positivistic research that leads to an interpretive paradigm with a transcendental phenomenological approach. This approach can explore the meaning of people who already have experience with CSR implementation of PT Amerta Indah Otsuka (AIO) Kejayan. The results show that this company's CSR in the form of the environment are village greening, nursery rooms, making Biopore holes, conservation of water catchment areas, revitalizing the Bangil City square, revitalizing the Malabar City forest, and the cleanest hamlet and city forest competition. The realization of the CSR program is carried out based on existing needs and problems so that the company can open-heartedly assist in the form of social responsibility. Suggestions for future researchers are to make a phenomenological study to the public who get and feel the CSR program from the company so that readers can know the benefits and objectives of implementing CSR.